Use and safety of appearance and performance enhancing supplements in gay, bisexual, and other men who have sex with men receiving daily tenofovir disoproxil fumarate/emtricitabine as HIV pre-exposure prophylaxis. Issue 4 (3rd April 2023) - Nhean, Salin; Tseng, Alice; Sheehan, Nancy L.; Bogoch, Isaac I.
ABSTRACT: Appearance- and performance-enhancing supplements (APES) may be associated with liver and renal toxicity, but use is often under-reported. This study describes the use and safety of APES among gay, bisexual, and other men-who-have-sex with men (gbMSM) attending an urban HIV pre-exposure prophylaxis (PrEP) clinic. A cross-sectional study was conducted between February 2018 to September 2018 to assess APES usage in gbMSM taking daily tenofovir disoproxil fumarate/emtricitabine for PrEP. Renal and liver function were assessed from electronic medical records. Among 50 participants (98% male, median 32 years, 52% White, on PrEP for a median 4.4 years), 72% reported lifetime APES use, with 52% currently using APES (median 1.5 products/person) and 28% never used APES. The most common products included whey protein, creatine supplements and anabolic steroids. The primary reason for APES use was to increase muscle mass. Three (12%) current APES users had elevated serum creatinine (stage 1) versus zero (0%) in the non-APES group. Two (8%) current APES users experienced grade 3–4 ALT/AST elevations versus zero (0%) in the non-APES group. APES usage among gbMSM taking PrEP was high and may be associated with liver/renal lab abnormalities. Increased awareness of APES use and potential toxicity is encouraged to enhance safety.